The study of possibility to elevate antitumor activity and decrease of systemic toxic effects of cisplatin by its binding with deliganded albumin - Sakhno, L.A.; Sarnatskaya, V.V.; Yushko, L.A.; Melnikov, O.R.; Momot, V.Ya.; Korneeva, L.N.; Svintsiskiy, V.S.; Korotich, V.G.; Nechitaylo, I.I.; Nikolaev, V.G. (Experimental Oncology, 2006)
Aim: To evaluate antitumor and toxic action of cisplatin (CP) in non-bound form and in a complex with deliganded albumin. Methods: To study complex-formation between CP and albumin, differential scanning and isothermic flow microcalorimetry were used. For quantitive evaluation of albumin-bound CP, the method of ultrafiltration was applied. Concentration of platinum in the samples was determined by atomic-absorption spectral analysis. Antitumor and toxic effect of CP and CP-albumin complex was studied in vivo using Guerin carcinoma (GC) model. Results: It has been shown that the second drug-binding site, located in the III domain of albumin molecule is one of the main points of binding of CP. Purification of officinal human serum albumin (HSA) on highly active carbon hemosorbents of HSGD mark allows to obtain deliganded albumin (dHSA) with elevated complex-forming ability toward CP. Administration of CP-dHSA complex provides higher rate of GC growth inhibition, than that of CP, and the content of creatinine in blood plasma of GC-bearing rats increases by 15% versus 40% in the case of CP administration. Conclusion: The data obtained allow recommend application of CP-dHSA to complex for enhancement of antitumor action and decrease of toxic effects of cisplatin.